The Future of AI-Integrated Project Management: A Structured Literature Review Based Risk Identification - Siddiqui, Muhammad Adnan; Wasif, Muhammad (International Journal of Engineering and Management Sciences, 2025)
The evolution of AI is changing the landscape of project management. The integration of AI into project management brings many advantages, yet it is also accompanied by prominent weaknesses and serious challenges. In addition, rapidly evolving technologies continue to transform the field’s dynamics. These evolving dynamics result in ambiguity about the current state of the field, and consequently, create an uncertainty regarding a roadmap for future advancements. The purpose of this paper is to address this challenge by developing a well-grounded conceptual insight that identifies the risks associated with AI adoption in project management, guiding both academia and industry towards a structured approach to its future advancements. This paper conducts a detailed structured literature review, adhering the PRISMA protocol, to evaluate the impact of AI on key facets of project management, its potential benefits and implementation challenges. Then it analyzes the literature and synthesizes the key findings. Finally, it conducts comprehensive analysis to identify both positive and negative risks i.e. opportunities and threats. This in-depth analysis and its findings enable us to understand the nature of the risks, and how those can be harnessed or mitigated to advance the field. Furthermore, it provides both academia and industry the foundation to plan improved risk mitigation strategies and to develop a structured adoption framework. This study is expected to make a significant contribution to the advancement of the field.